PRESERVATIVE ACTIVITIES OF EUCALYPTUS CITRIODORA ESSENTIAL OIL ON SOME PROCESSED FOODS (FUDMA JOURNAL OF SCIENCES, 2023)
The evaluation of plant constituents for antimicrobial and preservative activities on food products is part of the ongoing search for natural food preservatives. In line with that, detection of phytochemical constituents and evaluation of antimicrobial, GC – MS analysis and preservative properties of Eucalyptus citriodora essential oil on boiled white rice and bread was carried out using standard procedures. The results of the phytochemical screening revealed presence of saponins, tannins, flavonoids and phenolic compounds. Antibacterial activity of the E. citriodora oil showed highest zone of inhibition diameter against Shigella spp (21.66mm) while antifungal activity was more pronounced against Aspergillus fumigatus (31mm) using 100% oil. GC – MS analysis of the 100% petroleum ether fraction of the oil revealed compounds, which include cyclohexene and 1 – isopropyl – 2 – methylbenzene. Results of sanitizing activity of the 100% oil revealed 3.12 log count (cfu/g) reduction (bacteria), 3.22 log count (cfu/g) reduction (fungi) for boiled white rice and 1.50 log count (cfu/g) reduction (bacteria), 0.77 log count (cfu/g) reduction (fungi) for bread after 72 hours of storage. Results of organoleptic assessment and general acceptability showed that treatmentwith 50% w/w of oil revealed 74.4% likeness by judges as compared to 11.1% for control (untreated) after 96 hours (4 days) for boiled white rice and 61.1% likeness by judges as compared to 45.5% for control (untreated) after 96 hours (4 days) for bread. Findings from this study showed that E. citriodora essential oil possess antimicrobial and preservative activities on boiled white rice and
Keywords: Antimicrobial, Judges, Organoleptic, Preference, Preservative